ANALISIS PEMBEBANAN PAJAK HADIAH UNDIAN DALAM PROMOSI DENGAN PEMBERIAN HADIAH UNDIAN TERHADAP PERFORMA EARNING AFTER TAX BAGI PERUSAHAAN PERBANKAN. - Ismi Fathia Rachmi (Media Riset Akuntansi, Auditing & Informasi, 2006)
The purpose of this research Is to analyze the effect of promotion with raffle, also to analyze the implication towards the perfonnance of the company. Another analysis conducted in this research is the comparative between raffle tax borne by the winner or the granter. The research was conducted on 2 (two) banks whom raffle tax is borne by the granter and 3 (three) banks whom raffle tax is borne by the winner. From the research conducted, it can be summarized that both banks that promoted through raffle that the tax is borne by the granter experienced an increase in their sales volume each period. However, out of the three banks that promoted through raffle that the tax is borne by the winner, only 2 (two) experienced an increase in theirsales volume, while the other did not had an increase in sales volume. Both banks that borne their raffle tax were able to lowered theirsales and administration expense percentage toward sales, thus, increase theirproffl margin percentage. As forthe 3 banks that raffle tax are borne by the winner, were unable to lower their sales and administration expense percentage toward safes, thus, no increase of profitmargin percentage were obtained. The increase of sales volume experienced by both banks that borne their raffle tax are higher than those that borne the raffle tax to the winner. Out of the 5 banks researched, 4 of them had an increase in theireaming before tax and the contribution of marketing mix through promotion had made positive impact towards achieving company's goals.Keyword: Marketing, application of raffle tax